2019
DOI: 10.31223/osf.io/rnepc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of estimation methods for a nonstationary index-flood model in flood frequency analysis using peaks over threshold

Abstract: Accurate estimation of flood frequency is crucial for designing safe infrastructures. To reduce model uncertainty, threshold modeling techniques are often useful in bringing more valuable flood information into the analysis than traditional models based on annual maximum 15 discharges. Due to climatic or anthropogenic causes, changes in flood magnitudes in many parts of the world have been observed and are expected to continue in the future. To characterize such changes, nonstationary models have focussed on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 51 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…However, this study suggested further research on automated procedure in POT data construction under stationary condition with additional statistical arguments. Nonstationary POT based FFA has attracted more attention recently (Durocher et al 2019;Mostofi Zadeh et al 2019); however, the findings of these studies are not conclusive, and further research is warranted on nonstationary POT based FFA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, this study suggested further research on automated procedure in POT data construction under stationary condition with additional statistical arguments. Nonstationary POT based FFA has attracted more attention recently (Durocher et al 2019;Mostofi Zadeh et al 2019); however, the findings of these studies are not conclusive, and further research is warranted on nonstationary POT based FFA.…”
Section: Discussionmentioning
confidence: 99%
“…Quantile regression technique has been widely employed under AM model . Durocher et al (2019) compared four estimators based on index flood method and quantile regression technique including regression analysis, L-moments and likelihood method using POT data. Gupta et al (1994) noted that the coefficient of variation of AM flows should not vary with catchment area in a proposed region/group.…”
Section: Regional Flood Frequency Analysismentioning
confidence: 99%
See 3 more Smart Citations